2002
DOI: 10.1097/00000539-200206000-00035
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Training Value of Two Types of Anesthesia Simulators: Computer Screen-Based and Mannequin-Based Simulators

Abstract: We compared two different training simulators (computer screen-based versus full-scale) for training anesthesia residents to better document the effectiveness of such devices as training tools. This is an important issue, given the extensive use and the high cost of mannequin-based simulators in anesthesiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 12 publications
0
43
0
2
Order By: Relevance
“…The primary criterion in selecting the appropriate simulation technique and in designing the accompanying scenarios should be the ability to meet the training goals by providing learning experiences that are difficult to achieve in the actual work environment (Salas et al 1998, Nyssen et al 2002, Beaubien and Baker 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The primary criterion in selecting the appropriate simulation technique and in designing the accompanying scenarios should be the ability to meet the training goals by providing learning experiences that are difficult to achieve in the actual work environment (Salas et al 1998, Nyssen et al 2002, Beaubien and Baker 2004.…”
Section: Introductionmentioning
confidence: 99%
“…L'intérêt de la simulation comme outil d'évaluation formative a été démontré, permettant une meilleure application des recommandations dans la prise en charge de certaines pathologies spécifiques pour les étudiants [17]. La simulation permet également d'améliorer la rapidité de diagnostic et d'assurer une meilleure prise en charge technique des situations de crise [18,19]. Nos résultats confortent ces données qui avaient été initialement rapportées dans une population de médecins anesthésistes mis en situation critique dans le contexte du bloc opératoire.…”
Section: Discussionunclassified
“…A study involving testing pre-Gas Man and post-Gas Man usage showed that knowledge improved significantly in anesthesia residents at a university teaching center and at an MS-affiliated community hospital. 47 The Anesthesia Simulator was initially developed at the University of Washington by Howard Schwid and Dan O'Donnell (Simcord). 25 Since the year 2000, Anesoft Corporation has continued to develop the software and associated case library.…”
Section: Screen-based Simulators For Anesthesiologymentioning
confidence: 99%